Semantic indexing modelling of resources within a distributed system. (1st January 2013) - Lai, C.; Moulin, C.
This paper is concerning issues regarding the semantic indexing of resources in a peerto- peer network. An important requirement is a good quality of the discovery (i.e. the selection of results very related to a specific request) and a short response time. Keys used for indexing and the corresponding URLs of indexed resources are stored in a Distributed Hash Table (DHT) scattered among the different peers of a community. A key of indexing is a semantic description of resources and refers to elements belonging to ontologies of domain and to knowledge bases. We propose a model of indexing patterns in order to generate keys. It is used to guide users for producing assertions about their resources. It induces navigation inside ontologies presented in graphical user interfaces in a friendly and easy to use way. With different examples, we present the main cases of key generation that define the indexing context of a resource. We also describe experiments performed in test environments simulating various situations.